IMPLEMENTATION OF THE WAKALAH BIL UJRAH AGREEMENT IN SHARIA LIFE INSURANCE INDONESIA AND MALAYSIA - Hudayberdiyev, Muhammet (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2024)
This study examines the increase in public awareness in Indonesia and Malaysia about the importance of insurance, especially Sharia insurance, which both Muslims and non-Muslims prefer because its system is more transparent and fair. Even though public interest in these three countries is increasing, public knowledge about Sharia insurance is still limited. This research aims to understand the implementation of the Wakalah bi al-Ujrah contract in Prudential Sharia life insurance products, analyze its compliance with Islamic law and related fatwas, and identify supporting factors and challenges in its implementation. Using qualitative methods with a descriptive-analytical approach, data was collected through documentation and interviews. The research results show that implementing the Wakalah bi al-Ujrah agreement at Sharia Insurance involves key elements such as the Sharia Participant Application Form (SPAJ), policy summary, general and special terms and conditions, and policy illustrations. This study concludes that the implementation of the Wakalah bi al-Ujrah contract is by Islamic law, because SPAJ regulates the payment of Tabarru contributions and the management of funds based on the Wakalah bi al-Ujrah contract, guaranteeing transparency and fairness in the Wakalah bi al-Ujrah contract. insurance fund management